2021
DOI: 10.3892/ijmm.2021.5019
|View full text |Cite
|
Sign up to set email alerts
|

Protective effects of andrographolide against cerebral ischemia‑reperfusion injury in mice

Abstract: Ischemic stroke is one of the most common causes of mortality worldwide and is a primary cause of disability and mortality in adults. There is an unmet need for drugs that can effectively treat ischemic stroke. Hence, the present study explored the neuroprotective effects of andrographolide (Andro) in a mouse model of bilateral common carotid artery occlusion, and systematically evaluated the potential mechanisms underlying its effects. The effects of Andro on mouse brain tissue following cerebral ischemia-rep… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(11 citation statements)
references
References 28 publications
1
10
0
Order By: Relevance
“…However, Andro treatment significantly increased the expression of GAP43 in the injured tissues and decreased the number of astrocytes, which in turn mitigated glial scarring and promoted axonal regeneration, eventually bridging the gaps at lesion sites and restoring tissue continuity. These results are consistent with previous findings (Liang et al, 2017;Li et al, 2021).…”
Section: Discussionsupporting
confidence: 94%
“…However, Andro treatment significantly increased the expression of GAP43 in the injured tissues and decreased the number of astrocytes, which in turn mitigated glial scarring and promoted axonal regeneration, eventually bridging the gaps at lesion sites and restoring tissue continuity. These results are consistent with previous findings (Liang et al, 2017;Li et al, 2021).…”
Section: Discussionsupporting
confidence: 94%
“…A previous study showed that the administration of Dex in critically ill patients could improve cardiovascular and ventilatory outcomes during the intensive care unit stay (Castillo et al, 2019). Several other studies have shown that Dex exerts protective effects against apoptosis, necrosis, and autophagy in the brain both in vitro and in vivo (Cui et al, 2015;Kong et al, 2017;Liu et al, 2020). Dex has been shown to attenuate early brain injury in rats with SAH by suppressing the activation of the TLR4/NF-κB pathway (Yin et al, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…Brain tissue was extracted and weighed, and normal saline was added to prepare 10% tissue homogenate as described previously [ 15 ]. The tissue homogenate was centrifuged at 3000 rpm for 15 min at 4 °C, and the supernatant was taken and stored at −20 °C.…”
Section: Methodsmentioning
confidence: 99%